2015
DOI: 10.1002/bmc.3514
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cinnabarinic acid from culture fluid with magnetic microbeads

Abstract: In this study, antimicrobial pigment cinnabarinic acid (CA) was produced from Pycnoporus cinnabarinus in laboratory-scale batch cultures. Magnetic poly(ethylene glycol dimethacrylate-N-methacryloyl-l-tryptophan methyl ester) [m-poly(EGDMA-MATrp)] beads (average diameter = 53-103 µm) were synthesized by copolymerizing of N-methacryloyl-l-tryptophan methyl ester (MATrp) with ethylene glycol dimethacrylate (EGDMA) in the presence of magnetite (Fe3O4) and used for the adsorption of CA. The m-poly(EGDMA-MATrp) bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…CA is one of the most important phenoxazinones, which has antifungal, algicidal, and antiprotozoal/antimalarial activities (Eggert , 1995, 1997Göçenoğlu et al, 2015). P. cinnabarinus and animals typically produce CA, which is formed by the polymerization of two molecules of HAA (Eggert et al, 1995;Fazio et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA is one of the most important phenoxazinones, which has antifungal, algicidal, and antiprotozoal/antimalarial activities (Eggert , 1995, 1997Göçenoğlu et al, 2015). P. cinnabarinus and animals typically produce CA, which is formed by the polymerization of two molecules of HAA (Eggert et al, 1995;Fazio et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…humans (Nishizuka & Hayaishi, 1963). CA was also purified from the culture broth of Pycnoporus cinnabarinus and its antifungal, algicidal, and antiprotozoal/antimalarial activities were demonstrated (Eggert, Temp, & Eriksson, 1997;Eggert, Temp, Dean, & Eriksson, 1995;Göçenoğlu, Osman, Kara, Pazarlioglu, & Beşirli, 2015). It has recently been reported that CA may be involved in controlling autoimmune responses and reinforcing regulatory T cells activity, providing a new approach for the treatment of neuroinflammation (Fazio et al, 2012(Fazio et al, , 2014.…”
mentioning
confidence: 99%
“…There are, however, reports that CA is also produced in the orange dead leaf butterfly Kallima inachus , where its decrease triggers the larva-to-pupa transition [ 55 ]. CA has also been found deposited in the fruiting bodies of saprophytic white rod fungi from the Polyporaceae family in, among others, Pycnoporus cinnabarinus and Pycnoporus sanguineus [ 56 , 57 , 58 , 59 ] and in southern cinnabar polypore ( Trametes coccinea ) [ 60 ]. In the fungus Pycnoporus cinnabarinus , CA is created through the laccase-mediated oxidation of 3-hydroxanthranilic acid [ 57 , 59 ], and it is the presence of CA that gives these mushrooms their characteristic brick-brown color.…”
Section: Chemistry and Molecular Targets Of Cinnabarinic Acidmentioning
confidence: 99%
“…In the fungus Pycnoporus cinnabarinus , CA is created through the laccase-mediated oxidation of 3-hydroxanthranilic acid [ 57 , 59 ], and it is the presence of CA that gives these mushrooms their characteristic brick-brown color. CA is considered a natural pigment, and its isolation from Pycnoporus cinnabarinus culture media at the laboratory scale has been described [ 60 ].…”
Section: Chemistry and Molecular Targets Of Cinnabarinic Acidmentioning
confidence: 99%
“…39 The advent of synthetic organic polymers has transformed the production of specialized sorbents, offering selective adsorption of various molecules and ions at low manufacturing costs, with extensive surface areas, and strong thermal and mechanical properties. [40][41][42][43][44] These sorbents' customizable features have led to widespread use in environmental cleanup, food safety, and biomedical fields, notably in isolating and purifying vital biological molecules like enzymes and nucleic acids for therapeutic and diagnostic purposes. [45][46][47] The versatility of functionalized organic polymers also supports the development of innovative MIPs, with modifications for targeted selection capabilities.…”
Section: Introductionmentioning
confidence: 99%